2010
DOI: 10.1051/0004-6361/201014157
|View full text |Cite
|
Sign up to set email alerts
|

Doppler imaging of the helium-variable star a Centauri

Abstract: Aims. The helium-peculiar star a Cen exhibits interesting line profile variations of elements such as iron, nitrogen and oxygen in addition to its well-known extreme helium variability. The objective of this paper is to use new high signal-to-noise, high-resolution spectra to perform a quantitative measurement of the helium, iron, nitrogen and oxygen abundances of the star and determine the relation of the concentrations of the heavier elements on the surface of the star to the helium concentration and perhaps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
(66 reference statements)
1
23
0
Order By: Relevance
“…Nevertheless, on comparing [12], from which we found i = 71°, which is essentially the same as the value, i = 70°, from Ref. The magnetic field Be was measured using lines of hydrogen [12] and of helium [13]. This orientation of the star is fairly convenient for studying the magnetic field distribution and the distribution of chemical elements over its surface.…”
Section: Hd 75049 (Srcreu)supporting
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, on comparing [12], from which we found i = 71°, which is essentially the same as the value, i = 70°, from Ref. The magnetic field Be was measured using lines of hydrogen [12] and of helium [13]. This orientation of the star is fairly convenient for studying the magnetic field distribution and the distribution of chemical elements over its surface.…”
Section: Hd 75049 (Srcreu)supporting
confidence: 80%
“…It is interesting to use some calculated distributions [13] , i.e., near the negative pole. Thus, the behavior of this star is fully consistent with data for, e.g.,…”
Section: Hd 75049 (Srcreu)mentioning
confidence: 99%
“…If irot is already known, this can be used to constrain the allowable values of R * . Bohlender et al 2010). Asteroseismic and DI constraints are also available for several other stars (HD 37776, HD 43317, HD 149438, HD 184927;Kochukhov et al 2010;Pápics et al 2012;Donati et al 2006;Yakunin et al 2015); however, in these cases identical results were found directly from the stellar and rotational properties.…”
Section: B2 Close Binariesmentioning
confidence: 90%
“…BRH show that this variation occurs because of helium-rich and helium-poor areas on the stellar surface, which they have mapped using Doppler imaging. Interestingly, BRH identify 3 He, found in other helium-weak stars such as the highly unusual phosphorus-gallium star 3 Cen A (Castelli et al 1997;Adelman & Pintado 2000).…”
Section: Introductionmentioning
confidence: 94%